Nanoselenium prevents eimeriosis-induced inflammation and regulates mucin gene expression in mice jejunum - Alkhudhayri AA; Dkhil MA; Al-Quraishy S (International Journal of Nanomedicine, 2018)
Abdulsalam A Alkhudhayri,1 Mohamed A Dkhil,1,2 Saleh Al-Quraishy1 1Department of Zoology, College of Science, King Saud University, Riyadh, Saudi Arabia; 2Department of Zoology and Entomology, Faculty of Science, Helwan University, Cairo, Egypt Background: Although elemental selenium has been found to be effective against Eimeria, no study has yet investigated the effects of selenium nanoparticles (SeNPs) on the Eimeria parasite. The aim of this study, therefore, was to evaluate the ameliorative effect of SeNPs compared with elemental selenium on mice jejunum infected with sporulated oocysts of Eimeria papillata.Methods: The mice were divided into 4 groups, with the first being the non-infected, control group, and the second, third, and fourth groups being orally inoculated with 1,000 sporulated oocysts of E. papillata. The third and fourth groups also received, respectively, an oral dose of 0.1 mg/kg sodium selenite and 0.5 mg/kg SeNPs daily for 5 consecutive days.Results: The infection induced severe histopathological jejunal damage, reflected in the form of destroyed jejunal mucosa, increased jejunal oxidative damage, a reduction in the number of jejunal goblet cells, and increased production of pro-inflammatory cytokines, quantified by real-time polymerase chain reaction. Treatment of mice with SeNPs significantly decreased the oocyst output in the feces by ~80%. Furthermore, the number of parasitic stages counted in stained jejunal paraffin sections was significantly decreased after the mice were treated with SeNPs. In addition, the number of goblet cells increased from 42.6±7.3 to 95.3±8.5 cells/10 villus-crypt units after treatment. By day 5 post-infection with E. papillata, SeNPs could be seen to have significantly increased the activity of glutathione peroxidase from 263±10 to 402.4±9 mU/mL. Finally, SeNPs were able to regulate the gene expression of mucin 2, interleukin 1β, interleukin 6, interferon-γ, and tumor necrosis factor α in the jejunum of mice infected with E. papillata.Conclusion: The results collectively showed that SeNPs are more effective than sodium selenite with regard to their anti-coccidial, anti-oxidant, and anti-inflammatory role against eimeriosis induced in the jejunum of mice. Keywords: selenium nanoparticles, eimeriosis, jejunum, mice, inflammation, mucin 2 gene